Lichen spinulosus - Sobjanek, Michał; Sikorska, Monika; Sokołowska-Wojdyło, Małgorzata; Nowicki, Roman (Dermatology Review/Przegląd Dermatologiczny, 2014)
Introduction . Lichen spinulosus is a rare, benign dermatosis representing follicular keratotic disorders. It is characterized by follicular keratotic papules grouped into large patches. Symmetrical and often asymptomatic lesions affect the limbs, trunk, neck and very rarely the face. The etiopathogenesis of lichen spinulosus is unclear. The disease has been reported predominantly in children in the second decade of life, more frequently in boys. For the treatment keratolytics and emollients are mainly used. Topical corticosteroids, retinoids, tar preparations and vitamin D analogs are also useful. The disease has not been reported in Polish medical literature. Objective . Presentation of child with lichen spinulosus and review of the literature. Case report. An 8-year-old, generally healthy boy presented for a couple of years symmetrical, small spinous papules grouped into patches. Lesions affected the knee and shins. Hyperkeratotic lesions on the eyelids and nose were also observed. Histopathology showed dilated hair follicles with keratotic plugs and mild lymphocytic infiltration. According to clinical and histopathological features, the diagnosis of lichen spinulosus was established. The patient was treated with keratolytics and emollients with partial remission. Conclusions . Lichen spinulosus is a rare dermatosis which should be differentiated from other follicular keratotic disorders as well as nummular eczema, lichen planopilaris, frictional childhood eruptions, miliary pustular syphilis and psoriasis.